Constructing resilience through security and surveillance: The politics, practices and tensions of security-driven resilience. (February 2015) - Coaffee, Jon; Fussey, Pete
This article illuminates how, since 9/11, security policy has gradually become more central to a range of resilience discourses and practices. As this process draws a wider range of security infrastructures, organizations and approaches into the enactment of resilience, security practices are enabled through more palatable and legitimizing discourses of resilience. This article charts the emergence and proliferation of security-driven resilience logics, deployed at different spatial scales, which exist in tension with each other. We exemplify such tensions in practice through a detailed case study from Birmingham, UK: 'Project Champion' an attempt to install over 200 high-resolution surveillance cameras, often invisibly, around neighbourhoods with a predominantly Muslim population. Here, practices of security-driven resilience came into conflict with other policy priorities focused upon community-centred social cohesion, posing a series of questions about social control, surveillance and the ability of national agencies to construct community resilience in local areas amidst state attempts to label the same spaces as 'dangerous'. It is argued that security-driven logics of resilience generate conflicts in how resilience is operationalized, and produce and reproduce new hierarchical arrangements which, in turn, may work to subvert some of the founding aspirations and principles of resilience logic itself.